Modification of the existing maximum residue levels for fludioxonil in rhubarbs - Anastassiadou, Maria (EFSA J, 2019)
In accordance with Article 6 of Regulation (EC) No 396/2005, the Agriculture and Horticulture Development Board (AHDB) submitted a request to the competent national authority in the United Kingdom to modify the existing maximum residue level (MRL) for the active substance fludioxonil in rhubarbs. The data submitted in support of the request were found to be sufficient to derive an MRL proposal of 0.7 mg/kg for rhubarbs. Adequate analytical methods for enforcement are available to control the residues of fludioxonil in the plant matrix under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the long‐term intake of residues resulting from the use of fludioxonil according to the reported agricultural practice is unlikely to present a risk to consumer health.